Transcriptional regulation of the tyrosine hydroxylase gene by glucocorticoid and cyclic AMP. - Lewis, E J (1987)
Glucocorticoid and cyclic AMP increase tyrosine hydroxylase (TH) activity and mRNA levels in pheochromocytoma cultures. The transcriptional activity of the TH gene, as measured by nuclear run-on assay, is also increased when cultures are treated with the synthetic glucocorticoid dexamethasone or agents that increase intracellular cyclic AMP, such as forskolin and 8-BrcAMP. Both inducers effect transcriptional changes within 10 min after treatment and are maximal after 30 min for forskolin and after 60 min for dexamethasone. The 5' flanking sequences of the TH gene were fused to the bacterial gene chloramphenicol acetyltransferase (CAT), and the hybrid gene was transfected into pheochromocytoma cultures and GH4 pituitary cells. In both cell lines, a region of the TH gene containing bases -272 to +27 conferred induction of CAT by cyclic AMP, but not by glucocorticoid. The same results were found when a region of the TH gene containing -773 to +27 was used. Thus, the sequences required for induction of TH by cyclic AMP are contained within 272 bases of 5' flanking sequence, but sequences sufficient for glucocorticoid regulation are not contained within 773 bases.